Analisis Perbedaan Trend Harga Antara Warung Nasi Padang dan Warteg - Aqmal Maulana Sidik; Tadkirotun Nakiya; Syamsul Hidayat (Jurnal Manajemen Riset Inovasi, 2025)
This study is about price trends in two traditional Indonesian food stalls between Warung Nasi Padang and Warteg. Based on a survey of 51 customers, they found that price differences can be caused by basic factors; operational costs, raw material prices and consumer preferences. The result of this study is that the characteristics of Nasi Padang can be seen in stable prices and competitive strategies, while the characteristics of Warteg are more affordable and flexible. This difference affects the management strategy, which provides suggestions to improve productivity and competitive pricing.